Eight grade text book evaluation by Cunningsworth’s theory - Lia Arswin Apriyani; Rr. Hasti Robiasih (Journal of English Language and Pedagogy, 2019)
The objectives of this study are to: (1) describe the appropriateness of textbooks of the eighth grade based on the criteria of good textbook by Cunningsworth, and (2) describe the strength and weaknesses of each textbook. This research belongs to evaluation research. The object of this research was two textbooks. They are When English Rings a Bell and Bright for the eighth grade junior high school. The research adapted Cunningsworth’s theory of a good textbook to evaluate these textbooks. The data were taken from document analysis and interview. The steps of the research were data condensation, data display, drawing, and verifying conclusions. The results of the research were (1) When English Rings a Bell fulfills three criteria of a good textbook by Cunningsworth; they are topic, teachers’ book, and practical consideration. Bright meets seven criteria by Cunningsworth: aims and approaches, design and organization, language content, skills, topic, methodology, and practical consideration. (2) The strengths of When English Rings a Bell are in terms of appearance, topics, activities, and social and cultural context. Bright has strength in terms of topic, activities, social and cultural context, and media.  On the other hand, When English Rings a Bell contains some weaknesses in terms of skills, authentic resource, and content. It does not cover four skills, authentic reference for listening, and complete materials. Bright presents unattractive colouring, an expensive price, and less local, social, and cultural context.